The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.7224/1537-2073.2014-114
|View full text |Cite
|
Sign up to set email alerts
|

Critical Appraisal of Evidence for Improving Gait Speed in People with Multiple Sclerosis

Abstract: Background: Research has not yet compared the treatment effects of dalfampridine with traditional rehabilitation of gait impairments in multiple sclerosis (MS). The purpose of this review was to critically appraise the evidence for dalfampridine and gait training for increasing gait speed in people with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The gait speed improvements we observed with this combined intervention also exceed those that have been reported for exercise and gait training interventions in people with MS. 5,14 For example, a pooled analysis of task-specific gait training interventions in people with MS found an overall improvement in self-selected gait speed of 0.06 (95% CI, 0.02-0.10) m/s, 14 whereas the participant in this study had a 0.23-m/s increase in selfselected gait speed during the D-ER + PT phase. A meta-analysis of exercise interventions found only a small, nonsignificant improvement in T25FW time (-0.59 [95% CI, -2.55 to 1.36] seconds), 5 whereas our participant improved T25FW time by 0.90 seconds with the combined intervention.…”
Section: Plummer Et Almentioning
confidence: 58%
“…The gait speed improvements we observed with this combined intervention also exceed those that have been reported for exercise and gait training interventions in people with MS. 5,14 For example, a pooled analysis of task-specific gait training interventions in people with MS found an overall improvement in self-selected gait speed of 0.06 (95% CI, 0.02-0.10) m/s, 14 whereas the participant in this study had a 0.23-m/s increase in selfselected gait speed during the D-ER + PT phase. A meta-analysis of exercise interventions found only a small, nonsignificant improvement in T25FW time (-0.59 [95% CI, -2.55 to 1.36] seconds), 5 whereas our participant improved T25FW time by 0.90 seconds with the combined intervention.…”
Section: Plummer Et Almentioning
confidence: 58%
“…77,78 Two fair-quality quasiexperimental studies compared an aerobic exercise with usual care in adolescents with CP over 8 weeks (n=44 total). 88,132 VO2 peak measured in ml/kg/min was increased significantly more with cycle-ergometry in one study, and in both studies VO2 peak measured in ml/min was increased significantly with aerobic exercise (Table 43) (SOE: low). In participants with SCI, three studies reported VO2 peak, with two fair-quality RCTs (n=71) finding a significant increase with aerobic exercise training, 92,140 and a small (n=17), fair-quality cohort study not finding a difference, although the endpoint values were higher in the aerobic exercise group (Table 44) (SOE: low).…”
Section: Aerobic Exercises Versus Usual Carementioning
confidence: 93%
“…Forty-two studies (36 RCTs, 5 quasiexperimental studies, and 1 cohort study) evaluated the effect of physical activity on intermediate outcomes. 53,63,[75][76][77][78]82,88,89,[91][92][93]117,125,[132][133][134][135][136][137]140,147,186,198,204,[206][207][208][209][211][212][213][216][217][218][219][220][221][222]224,227,228,230,231,[234][235][236][237]242,243,246,247,249 Eighteen studies enrolled participants with MS (n=984), 53,63,[76][77]…”
Section: Kq2b: Intermediate Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing evidence supports the efficacy of D-ER for improving mobility (based on walking speed), but the beneficial effects only occur in a subset of persons with MS (i.e., responders). Responder status was not related to demographic characteristics, disease duration, level of disability, baseline walking speed, type of MS, or use of DMDs [32]. This indicates that the differences in responsiveness may be related to the underlying mechanism of action of D-ER [23].…”
Section: Pharmacologic Therapiesmentioning
confidence: 99%